Decreasing the Incidence of Temper Tantrums in Preschool Age Children by Using the Right Parenting (JURNAL KEPERAWATAN, 2022)
Temper tantrum is an explosion of uncontrolled anger. The peak temper tantrum in children occurs at the age of 3-4 years. One of the temper tantrum is caused by parenting style. This study aims to determine the relationship of parenting style to the incidence of temper tantrum in preschool children at An-Namiroh 7 Kindergarten Pekanbaru. Type of research is quantitative analytic observational cross-sectional method. The sample were parents who had preschool children (3-4 years old) totaling 39 childrens, using non probability sampling method with purposive sampling technique. Data collection using questionnaire. Data analysis techniques using Chi-Square test. The statistical test results showed a value of ρ value of 0.037, meaning that there is a relationship between parenting style to the incidence of temper tantrums in preschool children in An-Namiroh 7 kindergarten Pekanbaru. Thus, this research can be used as information for parents in providing the best parenting for their children